Guidance of longitudinally projecting axons in the developing central nervous system - Sakai, Nozomi; Kaprielian, Zaven (Frontiers in Molecular Neuroscience, 2012)
The directed and stereotypical growth of axons to their synaptic targets is a crucial phase of neural circuit formation. Many axons in the developing vertebrate and invertebrate central nervous systems (CNS), including those that remain on their own (ipsilateral), and those that cross over to the opposite (commissural), side of the midline project over long distances along the anterior-posterior body axis within precisely-positioned longitudinally-oriented tracts to facilitate the transmission of information between CNS regions. Despite the widespread distribution and functional importance of these longitudinal tracts, the mechanisms that regulate their formation and projection to poorly characterized synaptic targets remain largely unknown. Nevertheless, recent studies carried out in a variety of invertebrate and vertebrate model systems have begun to elucidate the molecular logic that controls longitudinal axon guidance.